2020
DOI: 10.1038/s41467-020-15886-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the spreading routes of lymphatic metastases in human colorectal cancer

Abstract: Lymphatic metastases are closely associated with tumor relapse and reduced survival in colorectal cancer (CRC). How tumor cells disseminate within the lymphatic network remains largely unknown. Here, we analyze the subclonal structure of 94 tumor samples, covering the primary tumors, lymph node metastases (LNMs), and liver metastases from 10 CRC patients. We portray a high-resolution lymphatic metastatic map for CRC by dividing LNMs into paracolic, intermediate, and central subgroups. Among the 61 metastatic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…Another investigation of the patterns of metastasis in colon cancer patients showed that liver metastasis could originate directly from the primary tumor or from LNMs. These data also showed the LNMs can also seed other LNs, including those in the same regional bed or more proximally (“skip spreading”) [ 145 ]. In addition, two back-to-back studies performed genomic analyses using breast cancer patient primary tumors and metastatic lesion samples to build the evolutionary history of the metastatic lesions.…”
Section: Lymph Node Metastasismentioning
confidence: 99%
“…Another investigation of the patterns of metastasis in colon cancer patients showed that liver metastasis could originate directly from the primary tumor or from LNMs. These data also showed the LNMs can also seed other LNs, including those in the same regional bed or more proximally (“skip spreading”) [ 145 ]. In addition, two back-to-back studies performed genomic analyses using breast cancer patient primary tumors and metastatic lesion samples to build the evolutionary history of the metastatic lesions.…”
Section: Lymph Node Metastasismentioning
confidence: 99%
“…Notably, lymphogenous spread is another prominent pathway for GIC ( 35 , 36 ). One study showed that MOC is related to retroperitoneal lymph node relapses.…”
Section: Metastatic Routementioning
confidence: 99%
“…Tumor metastasis is a complex process; one of the significant developmental program is EMT, which permits invasion and migration of cancer cells (Aiello et al, 2018;Pastushenko et al, 2018), and is associated with poor prognosis (Yang and Weinberg, 2008;Singh and Settleman, 2010;De Craene and Berx, 2013;Shang et al, 2019). Tumor progression is regulated by several biomolecules, whose mechanisms are mostly unknown (Zhang C. et al, 2020). Therefore, there is an urgent need to clarify the mechanisms underlying CRC progression.…”
Section: Introductionmentioning
confidence: 99%